Penggunaan Teknologi Artificial Intelligence Untuk Peningkatan Pembelajaran Pada SMA Nurul Iman Palembang Menggunakan ITIL V3 - Tata Sutabri; Niza Tadzkiratun Nafisah; Futri Maria; M. Ridho Amanatullah (FKOM UNIKU, 2024)
Artificial Intelligence (AI) is one of the technologies in today’s era that is very useful in its application. Artificial Intelligence (AI) is artificial intelligence which is a model of human intelligence which is a model of human intelligence that is applied in a machine for the manufacture of intelligent machines.In Fact,at this time we have to use technology that supports learning is really needed. The word of education requires innovation and creativity in order to realize learning that remains effective.The purpose of this article is to answer the question 1)is Artificial Intelligence (AI) important for learning?2) how is the use of artificial intelligence for learning?the article uses a qualitative method with data collection techniques with library research.